P542 RSV prophylaxis for prevention of recurrent childhood wheeze: a systematic review. (June 2019) - Quinn, Lauren; Shields, Michael; Groves, Helen
Abstract : Introduction: RSV-related lower respiratory tract infection (LRTI) has been associated with greater risk of recurrent wheezing and subsequent asthma. However, it is still unclear whether severe RSV infection is casual or rather has a shared susceptibility with asthma. There is an increased risk of asthma in those born late preterm. Palivizumab, a RSV-specific monoclonal antibody, reduces RSV-related hospitalisations in high-risk infants, but the longer term follow up has given conflicting evidence for the prevention of recurrent wheeze or asthma. We aimed to perform a systematic review and metanalysis to determine whether RSV prophylaxis (Palivizumab) reduced the risk of subsequent recurrent wheeze and asthma development. If prophylaxis (Palivizumab) reduces later wheeze/asthma risk, this would support the association between RSV and asthma as causative and might suggest that late preterms should also be offered prophylaxis (Palivizumab). Methods: An electronic advanced literature search was carried out across 4 main databases; Medline, Pubmed, Embase, Web of Science, and the Cochrane Library. The intervention being investigated was monoclonal antibody RSV prophylaxis and the outcome measured was recurrent wheeze/asthma development. Papers were screened to include primary studies of all study design type. Eligible studies were assessed for bias using the GRADE approach by 3 independent reviewers. Results: The overall meta-analysis was comprised of 7 studies (preterm birth N=5, follow-up >2 years N=5)), including randomised controlled trials (N=2), cohort/case control studies. Most studies were graded as having low quality evidence, due to the risk of bias, particularly reporting bias, as well as heterogeneity and inconsistency in baseline participant characteristics. Using a random effects model, the relative risk (RR) was 0.53 (95% Cl 0.25–1.09, p = 0.085). Although not statistically significant, this effect size is clinically significant in favour of Palivizumab reducing risk of recurrent wheeze. Consistent with the overall results we found a similar effect when subgroups of late-preterm or those followed for longer than 2 years were examined. Discussion: Although the results are not statistically significant, we found in this meta-analysis a clinically important reduction in RR. This supports the hypothesis that RSV prophylaxis reduces the risk of subsequent wheeze/asthma, demonstrating a potential causal relationship. Further studies are needed into the cost-effectiveness of RSV prophylaxis to prevent recurrent wheeze/asthma in late preterm births.